Sub-chronic exposure to second hand smoke induces airspace leukocyte infiltration and decreased lung elastance - Hartney, John M.; Chu, Hong Wei; Pelanda, Roberta; Torres, Raul M. (Frontiers in Physiology, 2012)
Exposure to second hand tobacco smoke is associated with the development and/or exacerbation of several different pulmonary diseases in humans. To better understand the possible effects of second hand smoke exposure in humans, we sub-chronically (4 weeks) exposed mice to a mixture of mainstream and sidestream tobacco smoke at concentrations similar to second hand smoke exposure in humans. The inflammatory response to smoke exposures was assessed at the end of this time by enumeration of pulmonary leukocyte infiltration together with measurements of lung elastance and pathology. This response was measured in both healthy wild type (C57BL/6) mice as well as mouse mutants deficient in the expression of Arhgef1 (Arhgef1–/–) that display constitutive pulmonary inflammation and decreased lung elastance reminiscent of emphysema. The results from this study show that sub-chronic second hand smoke exposure leads to significantly increased numbers of airspace leukocytes in both healthy and mutant animals. While sub-chronic cigarette smoke exposure is not sufficient to induce changes in lung architecture as measured by mean linear intercept, both groups exhibit a significant decrease in lung elastance. Together these data demonstrate that even sub-chronic exposure to second hand smoke is sufficient to induce pulmonary inflammation and decrease lung elastance in both healthy and diseased animals and in the absence of tissue destruction.